[List of Supporters and activities on unknown legislation] (Tufts Archival Research Center, 2007)
Missing Page(s); Confidential; Incomplete; List of organizations providing support on unknown legislation. Lists state legislatures that have passed supportive legislation and state agriculture commissioners who will submit statements. Provides names of farm groups that will provide statements or testimony, in which case names of testifiers are provided. Lists Business and Professional Groups, who have contacted Surgeon General, White House Public Liaison Office, and Office of Smoking and Health, in addition to those who will submit statements. Names labor groups that have submitted statements.